2019
DOI: 10.1097/olq.0000000000000957
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Spreading Human Immunodeficiency Virus Epidemic Among Older Males and Associated Factors: A Large-scale Prospective Cohort Study in Rural Southwest China

Abstract: Supplemental digital content is available in the text.Human immunodeficiency virus incidence was associated with males, older age, less than secondary schooling and not currently being married.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…This study found that younger people were more likely to be infected through NMNCHC, while older people were more likely to be infected through CHC. People over 50 years old are still sexually active, and they may seek sex with FSWs or casual partners, especially those who do not have spouses or stable sexual partners (17,18). The aphrodisiac usage promoted this behavior and enhanced the risk (19).…”
Section: Discussionmentioning
confidence: 99%
“…This study found that younger people were more likely to be infected through NMNCHC, while older people were more likely to be infected through CHC. People over 50 years old are still sexually active, and they may seek sex with FSWs or casual partners, especially those who do not have spouses or stable sexual partners (17,18). The aphrodisiac usage promoted this behavior and enhanced the risk (19).…”
Section: Discussionmentioning
confidence: 99%
“…Lower education and risk awareness levels among older PLWH may post challenges for effective implementation of HIV prevention and care. 5 Compared with younger adult cases, older PLWH in Chongqing were more likely to be divorced and had heterosexual transmission. These profiles of HIV epidemic in Chongqing reflect the epidemic across China.…”
Section: Discussionmentioning
confidence: 99%
“…3 A smaller but increasing share of older adult cases are attributable to new infections in later life. [4][5][6] Older PLWH may have different demographic and sociobehavioral profiles and clinical and immunological conditions, which affect outcomes of the disease. [7][8][9][10][11] Both patients and clinicians often underestimate the risk of HIV among older adults, and this low-risk perception may cause delays in HIV testing and diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From 1978, as commercial sex activity increased across the country [6], the proportion of newly reported HIV infections/acquired immune de ciency syndrome (AIDS) patients through heterosexual transmission increased dramatically. Nowadays, CRF07_BC and CRF08_BC have become the most epidemic strains in China [7,8] and drug-driven epidemic has been shifting to sexually transmission-driven epidemic [9]. There were other B/C CRFs reported in the last few years, such as CRF57_BC (identi ed in Baoshan, Western Yunnan) [10], CRF62_BC and CRF64_BC (identi ed in Ruili/Dehong, Western Yunnan) [11].…”
Section: Introductionmentioning
confidence: 99%